The Effect of Toddler Mother Class on Increasing Mother's Knowledge in Preventing Stunting - Rukmaini; Siauta, Jenny Anna; Wanti, Asri Retno (Rajaki of Tulip Medika Publisher, 2023)
Background: The World Health Organization (WHO) reports that the prevalence of stunting is around 151 million, accounting for 22.2% of the world's children. Stunting increases the risk of disease and death in children, adversely affects cognitive and motoric development, decreases school achievement, increases the risk of overnutrition and non-communicable diseases, and decrease productivity in adulthood. One reason is the mother's lack of knowledge about nutrition and health before, during, and after pregnancy. Objective : This study aims to determine The Effect of Toddler Mother Class on Increasing Mother's Knowledge in Preventing Stunting. Methodology: This study is a quantitative quasi-experiment with a one-group pretest-posttest design approach. Pretest-posttest knowledge measurement was carried out to respondents before and after have given a class of mothers under five about stunting. The sample in this study amount 114 with the total sampling technique. Data analysis using the paired T test. Results: The results showed that The pretest had a mean knowledge value was 8.91 std. division 2,011, while in the posttest had a mean value was 10.80 std. division 1,242. The value of p-value was 0.000, there is a significant difference in The Effect of Toddler Mother Class on increasing knowledge about stunting prevention. Conclusions and Suggestions: The results of the study showed a significant Effect of Toddler Mother Class on increasing the knowledge of mothers under five about stunting prevention.